Ectomesenchymal chondromyxoid tumor of the anterior aspect of the tongue - SEÇKİN GENÇOSMANOĞLU, DİLEK (MOSBY-ELSEVIER, 2008)
Ectomesenchymal chondromyxoid tumor of the anterior aspect of the tongue is a benign rare tumor. Thirty cases have been reported so far. It presents as a slowly growing, asymptomatic, submucosal nodule on the anterior dorsum Of the tongue. Histopathologically, the tumor is composed of a well-circumscribed, lobular proliferation of fusiform and ovoid bells in a chondromyxoid background. Most consistent immunohistochemical finding is the diffuse and strong immunoreactivity for glial fibrillary acid protein. Histogenetic origin of the tumor is uncertain. We report here a 56-year-old woman with a 0.7-cm tumoral lesion of 5 months duration on the anterior aspect of her tongue. Total excision was performed and histopathologic findings were consistent with ectomesenchymal chondromyxoid tumor. No recurrence was observed after 2 years of follow-up.